Deradicalizing Islamist Extremists - Rabasa, Angel (RAND Corporation, 2010)
Measures to prevent vulnerable individuals from radicalizing and to rehabilitate those who have already embraced Islamist extremism have been implemented in several Middle Eastern, Southeast Asian, and European countries. This monograph describes and assesses the strengths and weaknesses of these programs and proposes steps that can be taken to promote and accelerate deradicalization processes.